HUBUNGAN STRATEGI REKRUTMEN TENAGA PENDIDIK DAN PENGHARGAAN PRESTASI TERHADAP MOTIVASI KERJA DI SANGGAR GENIUS YATIM MANDIRI MAKASSAR - Isman Muhlis; M. Yusuf Tahir; Mardyawati Mardyawati (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Abstract:This research discuss the relation between teacher recruitment strategies and achievement awards toward work motivation at Sanggar Genius Yatim Mandiri Makassar with the aims: 1) to find out the teacher’s recruitment strategies at Sanggar Genius Yatim Mandiri Makassar; 2) to discover the teacher’s achievement awards Sanggar Genius Yatim Mandiri Makassar; 3) to determine the work motivation Sanggar Genius Yatim Mandiri Makassar; 4) to examine the correlation between teacherss recruitment and work motivation at Sanggar Genius Yatim Mandiri Makassar; 5) to examine the correlation between achievement awards and work motivation at Sanggar Genius Yatim Mandiri Makassar; and 6) to examine the correlation between the teacher’s recruitment, the achievement of work motivation toward work motivation at Sanggar Genius Yatim Mandiri Makassar. This research is a quantitative by ex post facto method. Instrument used is a questionarre than analyzed by using product moment correlation. This research indicate that: 1) the teacher’s recruitment strategy was in the very good category of the criteria set; 2) achievement awards for teachers were in the medium category 3) the teachers work motivation was in the medium category 4) the correlation between recruitment and selection of educators with work motivation showed a positive at a strong relation level; 5) the correlation between achievement awards for teachers with work motivation showed a positive and significant correlation at a moderate level of relation; 6) the correlation between recruitment and selection of teachers and achievement awards together with work motivation showed a positive and significant correlation at a strong relation level.